Localizing the SDGs in cities: reflections from an action research project in Bristol, UK. Issue 3 (16th March 2023) - Fox, Sean; Macleod, Allan
ABSTRACT: An increasing number of cities around the world are engaging with the UN Sustainable Development Goals (SDGs). How and why? We provide a critical reflection on SDG 'localization' derived from an action research project in the city of Bristol, UK. Through a research partnership with local government and non-governmental stakeholders we supported integration of the SDGs into local policy and urban monitoring efforts. Embedding the Goals in local policy making was largely a process of 'translation', which was achieved through a form of 'embedded advocacy' supported by a university-city partnership. We found that the Goals have local convening power, serve as a mechanism for building international city networks, and are instrumentalized by cities to signal global ambitions and progressive identities by embracing an internationally sanctioned policy agenda. New methods and frameworks for monitoring the SDGs are needed to fully realize the emerging 'subnational turn' in global policy.